P62 Improving health equity via the social determinants of health in the EU. (16th November 2010) - Lavin, T; Metcalfe, O
Abstract : Objective: Health inequalities between different socioeconomic groups persist throughout Europe. DETERMINE is a 3-year project supported by the European Commission which brings together a high level Consortium from 26 countries. Its objective is to support and enable policy makers and practitioners in all policy sectors to place a higher priority on health and health inequalities when developing policy. A frequent criticism of policy or action to address health inequalities and one that is particularly relevant in a worsening macroeconomic climate is that there has been insufficient economic analysis or inadequate adoption of an economic perspective in these areas. The DETERMINE project sought to address this deficit in a discrete work package strand coordinated by the Institute of Public Health in Ireland. Design: Using a specifically designed data collection instrument, examples of economic evaluations conducted on relevant policies and actions were identified and the benefits and barriers to using economic arguments in this area were explored. Setting: Data were collected by partners representing Belgium, Czech Republic, England, Estonia, Finland, Iceland, Netherlands, Northern Ireland, Norway, Poland, Republic of Ireland, Scotland, Slovenia, Spain and Wales. In addition, one partner collected data at the EU level (EuroHealthNet). Main Outcome Measures: The rationale is that where such work has been undertaken, results should be disseminated to influence decision-making in favour of addressing health inequalities. If such work has not been undertaken it is important to understand why this is the case. Results: Findings show that much work is occurring and there are examples of good practice. Barriers and opportunities to progressing work were identified and described by project partners. Conclusions: Economic arguments are a useful approach to tackling health inequalities when used in conjunction with a range of mechanisms. Our research showed diversity across Europe regarding the desire to use such an approach as well as availability of data and tools.